Celecoxib-mediated attenuation of non-alcoholic steatohepatitis is potentially relevant to redistributing the expression of adiponectin receptors in rats. Issue 7 (July 2022) - Zhu, Guoying; Chen, Li; Liu, Su; She, Ling; Ding, Yongnian; Yang, Changqing; Zhu, Fengshang
Abstract: Pharmacological inhibition of cyclooxygenase-2 (COX-2) activity ameliorated the severity of non-alcoholic steatohepatitis (NASH) rats. It is not completely understood that the role of COX-2 inhibitor celecoxib on adiponectin receptors (Adipo-R1/R2) expression in different tissues in NASH rats. Sprague-Dawley male NASH rats induced by a high-fat diet (HFD) were administrated with or without celecoxib for 8 weeks. Biochemical parameters of liver function, glucose, and lipid metabolism, and the levels of adiponectin, tumor necrosis factor-alpha (TNF-α), prostaglandin E2 (PGE2 ) in the serum or liver were collected according to the standard protocols. The mRNA and protein levels of Adipo-R1, Adipo-R2, and COX-2 in the liver, muscle, and visceral fat were performed by quantitative real-time polymerase chain reaction (q-PCR) and Western blot analysis, respectively. The results showed that celecoxib ameliorated the various clinical indicators and pathological characteristics in the NASH rats, including body weight, liver function, liver index, and redox activities in serum and hepatic samples. The serum concentrations of adiponectin and TNF-α and PGE2 were negatively correlated. As expected, these ameliorative effects of celecoxib were associated with the gene and protein levels up-regulation of Adipo-R1, Adipo-R2 in the liver and visceral fat tissues, and seeming to be compensatory down-regulation expression in muscle tissues ( P <0.05). Additionally, COX-2 protein expression was negatively correlated with serum adiponectin levels, protein expression of adiponectin receptors from the liver and visceral fat, conversely, positively correlated with those from the muscle. Our current study demonstrate that celecoxib might effectively alleviate NASH rats in a unique manner closely relevant to redistributing the expression of adiponectin receptors in the liver, visceral fat, and muscle. However, the precise molecular mechanism needs further study. Highlights: NASH is a watershed in the progression of NAFLD. Finding a therapy for NASH is in urgent need. Pharmacological inhibition of COX-2 activity ameliorated the severity of NASH. Low-dose celecoxib, a COX-2 inhibitor, can improve NASH by redistributing the expression of adiponectin receptors. Abstract : Celecoxib; Non-alcoholic steatohepatitis; Adiponectin; Adiponectin receptor.